CONCEPT OF “AUTHENTIC MATERIALS” AND THEIR VARIETIES - Ziyadulloyeva , Mokhidil Shovkat qizi (Educational Research in Universal Sciences, 2023)
The purpose of the article is to analyze the concept of authentic material and use of their varieties in language teaching.